Rehabilitation in patients with cerebellar ataxias - Hsin Fen Chien; Marise Bueno Zonta; Janini Chen; Giovana Diaferia; Celiana Figueiredo Viana; Hélio Afonso Ghizoni Teive; José Luiz Pedroso; Orlando Graziani Povoas Barsottini (Arquivos de Neuro-Psiquiatria)
ABSTRACT Cerebellar ataxias comprise a heterogeneous group of diseases characterized by motor and non-motor symptoms, which can be acquired, degenerative, or have a genetic cause, such as spinocerebellar ataxias (SCA). Usually, the genetic and neurodegenerative forms of cerebellar ataxias present a progressive and inevitable worsening of the clinical picture so that rehabilitation treatment is fundamental. Rehabilitation treatment includes physical therapy, respiratory therapy, speech, voice and swallowing therapy, occupational therapy, and new technologies, such as the use of exergames. The current treatment of patients with cerebellar ataxias, especially neurodegenerative forms, genetic or not, should include these different forms of rehabilitation, with the main objective of improving the quality of life of patients.